1977
DOI: 10.1002/chin.197716157
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: PARA‐SUBSTITUTED N‐ACETYL‐L(S)‐ AND ‐D(R)‐α‐AMINO‐N‐PHENYLGLUTARIMIDES. A STRUCTURE‐ACTIVITY STUDY OF SUBSTITUENT EFFECTS ON STEREOSELECTIVE ANTICONVULSANT ACTIVITY

Abstract: Früher beschriebene N‐Phenyl‐glutarimide (I) und (II) werden auf antikonvulsive Wirkung untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Based on these estimates, it was concluded that the 6-amino-1,4-oxazepane-3,5-dione derivatives are anticonvulsant compounds enough to be recommended for new anticonvulsant drug candidates. Witak., et al 1972.…”
Section: Resultsmentioning
confidence: 98%
“…Based on these estimates, it was concluded that the 6-amino-1,4-oxazepane-3,5-dione derivatives are anticonvulsant compounds enough to be recommended for new anticonvulsant drug candidates. Witak., et al 1972.…”
Section: Resultsmentioning
confidence: 98%